2016
DOI: 10.1016/j.ajem.2016.07.059
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in frequent ED use among those with multimorbid chronic diseases

Abstract: Objectives To examine the association between multi-morbid chronic disease and frequency of past six months emergency department (ED) visits, by gender, in a community sample of adults from North Florida (N=7,143). Methods Using logistic regression, we estimated associations between multi-morbid chronic disease and frequent ED use, using gender as an effect modifier. Results Multi-morbid chronic disease was associated with frequent ED use overall, with a stronger association among males. Of the 7,143 respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 32 publications
(55 reference statements)
4
32
0
Order By: Relevance
“…The mean age of FEDU across studies varied from 38.7 to 51 years, and the 18 to 44 age group was the most prevalent among FEDU . Among all ED users, those in younger age groups were more likely to be FEDU compared with those who were equal to or older than 65 years of age .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The mean age of FEDU across studies varied from 38.7 to 51 years, and the 18 to 44 age group was the most prevalent among FEDU . Among all ED users, those in younger age groups were more likely to be FEDU compared with those who were equal to or older than 65 years of age .…”
Section: Resultsmentioning
confidence: 97%
“…Only one study that included children found that younger age was associated with FEDU . Another study found that the association of age with FEDU differed by gender, with male FEDU being older than male non‐FEDU and female FEDU being younger than female non‐FEDU on average …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent research indicates that the elderly and African Americans are among the most frequent ED users. [2,26] With these factors considered, the profile of frequent ED users may vary from hospital to hospital, necessitating creative collaborative nurse educational programs to promote positive patient care outcomes in this deceptively diverse population.…”
Section: Introductionmentioning
confidence: 99%